Caffeine ingestion before exercise improves prolonged intermittent-sprint performance of team-sport athletes in normobaric hypoxia - Li, W.; Cao, Z.; Chang, J.; Xue, R.; Liu, J.; Guo, L.; Cao, Y.; Girard, O. (Frontiers in Nutrition, 2026)
Purpose: To investigate whether caffeine ingestion before exercise enhances performance during a prolonged intermittent-sprint test (IST) under hypoxic conditions simulating team-sport activity.